Barriers to vaccination in immunocompromised children: A needs assessment in children with childhood-onset SLE and inflammatory bowel disease - Lloyd, Audrey R.; Ardura, Monica I.; Wise, Kelly; Chavarin, Daniel J.; Boyle, Brendan; Sivaraman, Vidya (Frontiers in Pediatrics, 2023)
Background: Vaccination of immunocompromised children (ICC) remains suboptimal. Methods: Needs assessment surveys were administered to patients and caregivers during routine ambulatory visits to the rheumatology and gastroenterology clinics at Nationwide Children’s Hospital (NCH) from January 1 through August 31, 2018, and to community primary care physicians (PCPs) at their monthly meeting and electronically. Results: Completed surveys were received for 57 patients (31 with childhood-onset systemic lupus erythematosus (c-SLE) and 26 with inflammatory bowel disease (IBD)) and 30 PCPs. Of the patient cohort, 93% (n=53) felt their PCP was well informed about vaccines and 84% (n=47) received vaccinations from either their PCP or local health department. Two patient surveys noted concerns of vaccine safety. Among the 30 responses completed by PCPs 50% (n=15) preferred to provide all vaccines themselves, however, only 40% (n=12) of PCPs felt “very confident” when providing vaccines to ICC. Further, 83% (n=25) did not stock the 23-valent pneumococcal vaccine and only 27% (n=8) routinely recommended vaccination of household contacts. Conclusions: Our study found a discordance between parent and PCP comfort in vaccinating ICC, highlighting an important barrier to vaccination in this patient population. In our cohort of patients, vaccine hesitancy was not a barrier to vaccination.